Learning Approaches used by Different Applications to Achieve Deep Fake Technology - Maharjan, Ashish; Shakya, Asish (Journal of Innovation in Academia, 2023)
Deepfake technology is an emerging field that has gained considerable attention in recent years. Deepfakes are synthetic media, including images, videos, and audio recordings, that are manipulated by advanced machine learning algorithms to produce convincing yet entirely artificial content.  This paper explores the various applications and the technologies used by them to achieve deep fake. The machine learning algorithms and the software are used by each  of them for proper execution of the technology. Further, we discuss the future prospects of the deepfake technology and explore future directions for research and development in this area, including the need for improved detection and verification techniques and increased education and awareness among the public.